Grain rotation in 2d-hexagonal systems with competing interactions - Pignol, Ricardo Jorge (2007)
We look at a grain rotation mechanism in a bidimensional pattern forming system exhibiting an hexagonal phase. This mechanism is believed to be relevant in the coarsening process of a variety of physical systems with short- and long-range competing interactions. We focus on the Cahn-Hilliard model with thermal fluctuations. The grain rotation process is uncovered from the dynamical evolution of a misoriented circular grain surrounded by an otherwise perfect crystal.